2021
DOI: 10.1371/journal.pone.0260148
|View full text |Cite
|
Sign up to set email alerts
|

Association of anthropometric measures of obesity and physical activity with cardio-vascular diseases among older adults: Evidence from a cross-sectional survey, 2017–18

Abstract: Background With the increase in elderly population, the risk of cardiovascular diseases (CVD) among Indian older adults is also increasing. The present paper tries to assess how different anthropometric measures of obesity and physical activity affects cardiovascular disease risk among older adults in India. Methods The data from Longitudinal Ageing Study in India (LASI) has been used. The total sample size for the present study is 31,464 older adults aged 60 years and above. Chi-square test and binary logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The number of participants in included studies varied between 140 and 59 037 24 25. There were 25 (83.3%) included studies in India19 24–47 and three (10%) in Bangladesh 48–50. The remaining two studies were conducted in Mauritian51 and Pakistani52 populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of participants in included studies varied between 140 and 59 037 24 25. There were 25 (83.3%) included studies in India19 24–47 and three (10%) in Bangladesh 48–50. The remaining two studies were conducted in Mauritian51 and Pakistani52 populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two studies were conducted in Mauritian51 and Pakistani52 populations, respectively. The final analyses included two prospective cohort studies (one looking at HTN26 and one looking at CVD mortality51), four case-control studies44–47 (looking at CVD outcomes) and 24 cross-sectional studies19 24 25 27–43 48–50 52 (looking at HTN outcomes). In terms of exposure variables, 29 studies included BMI, 27 studies used WC, 21 studies used WHR and ten studies additionally used other measures, including WHtR (n=6) and hip circumference (n=2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A very large cohort study from India with a sample size of around 65 000 people demonstrated that the prevalence of CVD is high in India and women when compared with men have a higher risk of developing CVD 26. Results from the same cohort study revealed that physical inactivity and obesity increased the likelihood of CVD by 22% and 60%, respectively 27. Lifestyle-based interventions are the need of the hour to address these risk factors so that their impact on cognitive performance can be reduced.…”
Section: Discussionmentioning
confidence: 99%